Extracellular Matrix Signals as Drivers of Mitochondrial Bioenergetics and Metabolic Plasticity of Cancer Cells During Metastasis - Urra, Félix A.; Fuentes-Retamal, Sebastián; Palominos, Charlotte; Rodríguez-Lucart, Yarcely A.; López-Torres, Camila; Araya-Maturana, Ramiro (Frontiers in Cell and Developmental Biology, 2021)
The role of metabolism in tumor growth and chemoresistance has received considerable attention, however, the contribution of mitochondrial bioenergetics in migration, invasion, and metastasis is only recently being understood. Migrating cells adapt their energy needs to fluctuating changes in the microenvironment, exhibiting high metabolic plasticity. This occurs due to dynamic changes in the contributions of metabolic pathways to promote localized ATP production in lamellipodia and control signaling mediated by mitochondrial ROS. Recent evidence has shown that metabolic shifts towards reductive carboxylation, glutaminolysis, and phosphocreatine-creatine kinase pathways promote resistance to anoikis, migration, and invasion in cancer cells. Notably, these metabolic changes can be determined by changes in the composition and density of the extracellular matrix (ECM). ECM stiffness, integrins, and small GTPases Rho promote mitochondrial fragmentation, mitochondrial localization in focal adhesion complexes, and metabolic plasticity, supporting enhanced migration and metastasis. Here, we discuss the role of ECM in regulating mitochondrial metabolism during migration and metastasis, highlighting the therapeutic potential of compounds affecting mitochondrial function and selectively block migration.